Structures of inequality on Bronze Age Cyprus studies in honour of Alison K. South - Hulin, Linda; Crewe, Lindy; Webb, Jennifer M. (Astrom Editions, 2018)
This volume honours the very significant contribution to Cypriot archaeology made by Alison South, whose excavations at Kalavasos 'Ayios Dhimitrios' have revealed textbook evidence for complex society in the latter half of the Late Bronze Age.
Keywords: Vor- und Frühgeschichte; Archäologische Stätte; Zypern; Festschrift; Aufsatzsammlung